(untitled) (Bioresearch Communications, 2026)
Purpose: Burn injuries are a serious medical issue worldwide. In this study, Curcuma longa (CUR) loaded human amniotic membrane (HAM) gel was formulated to find an effective treatment for burn wounds with a faster healing rate and cost-effectiveness. Methodology: Physicochemical evaluation of the gel formulations was carried out through visual examination, assessing factors such as consistency, homogeneity, pH, FTIR, NMR analysis, and brine shrimp lethality test. To determine the burn wound healing efficacy, 20 female Wistar rats with 150-180g body weight were randomly divided into five groups: negative control, HAM, CUR, HAM+CUR and positive control. Burns were created and then treated with respective gels. Major findings: All gel formulations were essentially homogeneous and had good consistency with a pH between 6.68 and 6.80. FTIR and NMR studies supported the presence of collagen and skin irritation study displayed no edema or erythema after 7 days of topical application. After 16 days of treatment, the HAM+CUR group showed superiority (94.31±2.24 %) in burn wound healing, which was statistically the most significant compared to the control group (P<0.001). In addition, it takes only 19.67±1.52 days for the HAM+CUR group for re-epithelialization, while HAM, CUR, positive and the negative control group required 25.33±1.53, 24.67±2.08, 22.0±2, and 31.67 ±1.15 days for re-epithelialization, respectively. Histological evaluation revealed that HAM+CUR treated rat groups had significant epidermal regeneration, granulation tissue formation and collagen deposition. Conclusions: Therefore, HAM+CUR gel demonstrates significant potential therapeutic agent for treating burn wounds. Bioresearch Commu. 12(1): 1941-1952, 2026 (January)